Pengembangan Media Belajar Peti Ice Pada Pembelajaran Tematik Siswa Kelas 3 Sekolah Dasar - Rachman, Aditya; Hidayat, Muhammad (Jurnal Didaktika Pendidikan Dasar, 2023)
This research covers the process of developing and evaluating ICE Crate learning media in depth. This problem focuses on the stages of development, design, implementation, and measurement of the effectiveness of these learning media in improving the learning outcomes of grade 3 students in thematic learning. Through the PETI ICE learning media (Innovative Cycle Life and Decorative Thematic Learning), students are expected to be able to experience innovative learning. This study aims to improve student learning outcomes in thematic learning and describe the increase in student learning outcomes in thematic learning. The research methodology is classroom action research (CAR). The model in this study uses the Kemmis and Taggart implementation flow and the researchers use the R & D approach (research and development). The utilization of innovative media "PETI ICE" in thematic learning for grade 3 SD Bosowa Al-Azhar can improve student learning outcomes beyond the standard scores with 2 actions, namely in cycle I and cycle II. The results show that in Pre-Cycle the average score of knowledge is 60.00 and skills is 41.4, in Cycle I average score of knowledge is 76.00 and skills 62.6, in Cycle II the average score of knowledge 88.00 and skills 80.00. These make the innovative media "PETI ICE" able to improve student learning outcomes with a very satisfying percentage.